MicroRNA 135a Suppresses Lymph Node Metastasis through Down-Regulation of ROCK1 in Early Gastric Cancer - Shin, Ji-Young; Kim, Young-Il; Cho, Soo-Jeong; Lee, Mi Kyung; Kook, Myeong-Cherl; Lee, Jun Ho; Lee, Sang Soo; Ashktorab, Hassan; Smoot, Duane T.; Ryu, Keun Won; Kim, Young-Woo; Choi, Il Ju (PLOS ONE, 2014)
MicroRNAs (miRNAs) play a critical role in gastric cancer progression and metastasis. This study investigated the role of miRNA-135a in early gastric cancer (EGC) including lymph node (LN) metastasis. We examined the correlation between miRNA-135a expression and clinical outcomes in 59 patients who underwent surgery for EGC. Using gastric cancer cell lines, we performed functional and target gene analyses. miRNA-135a expression was down-regulated in 33.9% of patients. These patients showed a significantly more advanced stage (TNM stage≥IB, 35.0% vs. 12.8%, p = 0.045) and higher rate of LN metastasis (30.0% vs. 5.1%, p = 0.014) than those with up-regulation of miRNA-135a expression. In a multivariate analysis, down-regulation of miRNA-135a was an independent risk factor for LN metastasis (adjusted odds ratio, 8.04; 95% confidence interval, 1.08–59.81; p = 0.042). Functional analyses using gastric cancer cell lines showed that miRNA-135a suppressed cell viability, epithelial-mesenchymal transition, cell invasion, and migration. ROCK1 was a target of miRNA-135a and its expression was inversely correlated to that of miRNA-135a. ROCK1 expression was significantly increased in EGC patients with LN metastasis than in those without LN metastasis. Our results confirm the tumor-suppressive role of miRNA-135a, and demonstrate its role in LN metastasis in EGC. miRNA-135a and its target gene ROCK1 may be novel therapeutic and prognostic targets for EGC.